Application of two charge transfer complex formation reactions for selective determination of metformin hydrochloride in pharmaceuticals and urine - Nagaraju Rajendraprasad; Kanakapura Basavaiah (SpringerOpen, 2020)
Abstract Background Metformin hydrochloride (MFH) is a biguanide class anti-diabetic drug used to treat type-2 diabetes mellitus. Its reaction with two charge-transfer complexing agents, p-chloranilic acid (PCA) and 2,3-dichloro-5,6-dicyano-p-benzoquinone (DDQ) in acetonitrile medium to yield coloured products measurable at wavelengths of maxima 530.0 and 460.0 nm, respectively, was conveniently used to develop two spectrophotometric methods for analyses of bulk sample and tablets. Results The effect of solvent, reagent concentration and reaction time to form charge-transfer (CT) complexes was meticulously studied and optimized. Under optimised conditions, the absorbance at the respective wavelength of maximum versus concentration of MFH was in linear correlation for the range from 8.0 to 320.0 and from 1.6 to 64.0 μg mL-1 in PCA and DDQ methods, respectively, and correspondingly, the values of molar absorptivity of 0.733 × 103 and 0.257 × 104 L mol-1 cm-1 and Sandell sensitivity of 0.3620 and 0.0644 μg cm-2. The quantification (QL) and detection (DL) limits were 2.67 and 0.88 μg mL-1 for PCA method, and 0.33 and 0.11 μg mL-1 for DDQ method. Conclusion The new methods were emerged as repeatable and reproducible, with replicate measurements for intra- and inter-day variations as showed by obtained RSD values of < 2%. Within a day and between day relative errors were ≤ 2.18%. Methods were also validated for robustness, ruggedness and selectivity and agreeing results were produced. The methods were used to analyse MFH-containing tablets very accurately and precisely as reflected by the mean recovery value close to 100% and lower RSD values, respectively. Analysis of spiked human urine yielded excellent mean recoveries, indicating the absence of interference from endogenous substances.